Performance Study of Kindergarten School Supervisors in North Sulawesi Province - Suwaryaningrat, Ni Dewi Eka; Lumapow, Harol R.; Rawis, Joulanda A.M.; Lengkong , Jeffry Sony Junus (JR Education, 2024)
This research aims to analyze the relationship between work climate, discipline, and interpersonal communication on the performance of kindergarten school supervisors in North Sulawesi Province. The background to this research is based on school supervisors' important role in improving education quality through effective supervision. However, various problems were found, such as a lack of discipline, supervisory experience, and an unsupportive work climate, which impacted the performance of school supervisors. This research uses a survey method with a correlational approach. Data was obtained through questionnaires from 40 kindergarten school supervisors in North Sulawesi. The variables studied include work climate (X1), discipline (X2), interpersonal communication (X3), and school supervisor performance (Y). Data analysis was carried out using descriptive and inferential statistical techniques, with the help of the SPSS version 29 for Windows and Microsoft Excel 2021 programs. The research results showed that work climate, discipline, and interpersonal communication each had a strong positive correlation with supervisory performance. The coefficient of determination for work climate is 0.544, which means that 54.4% of the variation in supervisory performance can be explained by work climate. Discipline has a coefficient of determination of 0.435, indicating that 43.5% of the variation in supervisory performance can be explained by discipline. Interpersonal communication has a coefficient of determination of 0.582, indicating that 58.2% of the variation in supervisory performance can be explained by interpersonal communication. Simultaneously, these three variables have a significant relationship with the performance of school supervisors. Multiple regression analysis shows that the combination of a good work environment, high discipline, and effective communication overall improves the performance of school supervisors. The calculated F value is 35.743 with a significant probability level of less than 0.001, indicating that this regression model can be used to predict supervisor performance with a high level of confidence. This research suggests focusing on improving work climate, discipline, and interpersonal communication to improve supervisor performance, which contributes theoretically and practically to education in North Sulawesi.